ALIRAN ASY'ARIYAH (Kajian Historis dan Pengaruh Aliran Kalam Asy’ariyah) - Hasibuan, Hadi Rafitra (Jurnal Ilmiah Al-Hadi, 2017)
Asy'ariyah rapidly developed from the 11th century AD. Together with the spread of Sufism (Sufi), this understanding also gained support by rulers in several Islamic governments. Ash'ariyah became the official school of the Gaznawi dynasty in India in the 11th-12th century that caused this understanding to spread from India, Pakistan, Afghanistan, to Indonesia. Asy'ariyah's understanding is very strong in the body of Muslims and the aqidah continues to spread among Muslims. They do not realize that their understanding is a deviation from the auspices of Ahlus Sunnah wal Jamaah, a new idea that exists after the end of the main generation of people: companions, tabi'in, and tabi'in.